2022
DOI: 10.1167/iovs.63.13.8
|View full text |Cite
|
Sign up to set email alerts
|

The Matricellular Protein SPARC Decreases in the Lacrimal Gland At Adulthood and During Inflammation

Abstract: Purpose Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein abundantly expressed in basement membranes and capsules surrounding a variety of organs and tissues. It mediates extracellular matrix organization and has been implicated in cell contraction. Here, we evaluated the expression of SPARC in the murine lacrimal gland at adulthood and during inflammation. Methods Lacrimal glands of young mice (4–6 weeks old) and adult mice (32–40 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Jessica Feldt et al showed that SPARC, a novel blastocyte glycoprotein, is expressed by lacrimal myoepithelial cells. The lack of SPARC in adulthood may impair myoepithelial cell contraction and tear secretion [ 18 ]. Consequently, its involvement is closely associated with the occurrence and development of ocular diseases such as dry eye.…”
Section: Introductionmentioning
confidence: 99%
“…Jessica Feldt et al showed that SPARC, a novel blastocyte glycoprotein, is expressed by lacrimal myoepithelial cells. The lack of SPARC in adulthood may impair myoepithelial cell contraction and tear secretion [ 18 ]. Consequently, its involvement is closely associated with the occurrence and development of ocular diseases such as dry eye.…”
Section: Introductionmentioning
confidence: 99%